A bibliometric and content analysis of sustainable development in small and medium-sized enterprises. (1st February 2020) - Prashar, Anupama; Sunder M, Vijaya
Abstract: Research on sustainability or sustainable development has emerged significantly over the past two decades, evidenced by an increasing interest and publication momentum by academic scholars. Given the importance of small and medium sized enterprises (SMEs), that constitute ∼99% of all firms, this paper adopts a three-stage systematic review protocol to present a state of art literature review on sustainable development in SMEs. Four different analysis-synthesis approaches (bibliometric analysis, methodological analysis, qualitative content analysis, and logical reasoning of authors) were used on the literature data of 117 relevant papers (from 37 journals) identified from mainstream academic databases. This review provides insights not previously fully captured or evaluated by other reviews on this topic. The findings provide several implications on the current state of literature on sustainable development in SMEs, leading to research gaps and directions for future research. The findings provide a robust roadmap for further investigation in this field.